3,6-dimethyl ester-α-mangostin Compound Modified from Isolate α-mangostin Garcinia Mangostana Linn - Khoiriyah Umami; Arif Fadlan; Taslim Ersam (IPTEK Journal of Proceedings Series, 2020)
Isolate α-mangostin (1) is a phenolic compound derived from oxygenated and prenylated xanthones and major compounds obtained from the fruit peel of G. mangostana Linn., Which is stated to have inhibitory activity against α-glucosidase enzymes, serves to determine the antidiabetic activity resulting in IC50 value of 29,92 µM, is of the nature moderate to positive control (acarbose) with an IC50 value of 4.55 µM. A modified compound of α-mangostin (1) with acetic anhydride obtained by 3,6-di-methyl ester-α-mangostin (2) derivative showed the inhibitory value of α-glucosidase (IC50 13,89 μM), this value is better than the activity inhibition of α-mangostin (1), but not as active as the positive control value of the acarbose compound. The separation process to obtain α-mangostin isolates from the fruit peel of G. mangostana Linn was obtained by maceration method with ethyl acetate solvent, followed by refraction using a vacuum liquid chromatography (KCV) method over silica gel (Merck 60 G) and eluted using eluent (n-hexane: ethyl acetate) with increasing polarity, to produce as much pure crystal (21.66 g), yield (24%). While the structural characterization of the two compounds was carried out using UV-Vis, IR, HRESIMS, 1H-NMR and 13C-NMR spectroscopic methods, the antidiabetic testing was carried out using the α-glucosidase enzyme inhibition method.